Report - Bristol General Strike Committee, 11 May 1926 (page 1) (Bristol)
1926-05-11 "Report - Bristol General Strike Committee, 11 May 1926 (page 1)" [g0327001.jpg], 11 May 1926, Bristol General Strike Committee Local Organisation